Eine neue Löwenkopfsima aus Marmor des 5. Jhs. v. Chr. aus Selinunt - Albers, Jon; Miß, Axel (Römische Mitteilungen, 2024)
During the ongoing excavations in the area of the eastern harbour of Selinunte, a block of a sima with a lion's head made of marble was found in mid-August 2023. What makes this finding remarkable is on the one hand, that it is significantly larger than the other known marble sime in this region and that there has been no other comparison so far, which is why the question of the associated temple arises. Possibly the sima belongs to Temple E or an unknown building of classical times. Another striking feature is that the object is unfinished, i.e., it was never attached, and in this state, it will allow valuable conclusions to be drawn about the ancient building process. In the final consequence, the condition of the object therefore also allows very concrete indications of the trade and work contacts to Paros.